Предмет: Алгебра, автор: eto50mlradosty

1- Найди значение выражения

2 - Упрости выражение:

Приложения:

Ответы

Автор ответа: Applegate
3

 \bf \: 1). \:  \:  {x}^{2}  + 2x \sqrt{3}  + 11 = {( \sqrt{3} + 1) }^{2}  + (2( \sqrt{3}  + 1)( \sqrt{3} )) + 11 = 3 + 2 \sqrt{3}  + 1 + 2(3 +  \sqrt{3} ) + 11 = 15 + 2 \sqrt{3}  + 6 + 2 \sqrt{3}  = 21 + 4 \sqrt{3} ;  \\  \huge \bf \: otvet:21 + 4 \sqrt{3} . \\  \\  \bf \: 2). \:  \:  \sqrt{2}  \times (10 - 5 \sqrt{2} ) = 10 \sqrt{2}  - 10 = 10( \sqrt{2}  - 1); \\  \bf \huge \: otvet: \: 10( \sqrt{2}  - 1).

Похожие вопросы
Предмет: Алгебра, автор: vlad058